PENGARUH PENERAPAN MIND MAPPING BERBANTUAN CANVA TERHADAP HASIL BELAJAR MURID KELAS V PADA MATA PELAJARAN PENDIDIKAN PANCASILA GUGUS I LEMBAH SEGAR KOTA SAWAHLUNTO - Tiara Amelia; Reinita; Atri Waldi; Mansurdin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of Canva-assisted mind mapping media on the learning outcomes of fifth-grade students in Pancasila Education at Cluster I Lembah Segar, Sawahlunto City. The background of this research is the low learning outcomes of students caused by the monotonous use of instructional media, resulting in passive students who struggle to organize learning concepts independently. This study used a quantitative approach with quasi-experimental design (nonequivalent control group design). The sample consisted of 21 students from SDN 03 Aur Tajungkang as the experimental class and 20 students from SDN 05 Kubang Sirakuk Bawah as the control class, selected through purposive sampling. The research instrument was a 15-item multiple-choice test administered as pretest and posttest. Data were analyzed using N-Gain and Independent Sample T-Test via IBM SPSS Statistics 21. Results showed that the experimental class posttest mean (76.19) was higher than the control class (65.90). The experimental class N-Gain (0.53, moderate category) exceeded the control class (0.19, low category). Hypothesis testing yielded a significance value of 0.044 < 0.05, so H₀ was rejected and H₁ was accepted. Therefore, there is a significant effect of Canva-assisted mind mapping media on the Pancasila Education learning outcomes of fifth-grade students at Cluster I Lembah Segar, Sawahlunto City.